2020
DOI: 10.1042/bsr20200259
|View full text |Cite
|
Sign up to set email alerts
|

Tanshinone II A enhances pyroptosis and represses cell proliferation of HeLa cells by regulating miR-145/GSDMD signaling pathway

Abstract: Cervical cancer is the fourth most common cancer in women globally. Lack of effective pharmacotherapies for cervical cancer mainly attributed to an elusive understanding of the mechanism underlying its pathogenesis. Pyroptosis plays a key role in inflammation and cancer. Our study identified microRNA (miR) 145 (miR-145)/gasdermin D (GSDMD) signaling pathway as critical mediators in the effect of tanshinone II A on HeLa cells. In the present study, we found that treatment of tanshinone II A led to an obvious re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
25
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 37 publications
(27 citation statements)
references
References 43 publications
2
25
0
Order By: Relevance
“…The results showed that the expression levels of IL-18 and IL-1β were markedly increased (Fig. 2F), consistent with the results of a previous study (11). Notably, tanshinone IIA exhibits the opposite effect on normal cells and tumor cells, which may attribute to the different microenvironment.…”
Section: Resultssupporting
confidence: 91%
See 4 more Smart Citations
“…The results showed that the expression levels of IL-18 and IL-1β were markedly increased (Fig. 2F), consistent with the results of a previous study (11). Notably, tanshinone IIA exhibits the opposite effect on normal cells and tumor cells, which may attribute to the different microenvironment.…”
Section: Resultssupporting
confidence: 91%
“…Tanshinone IIA inhibits cell proliferation and enhances apoptosis of HK1 cells. Previous studies have demonstrated the anticancer effects of tanshinone IIA in cervical cancer (9,11). In the present study, the effects of tanshinone IIA on HK1 cells were assessed (Fig.…”
Section: Resultsmentioning
confidence: 85%
See 3 more Smart Citations